2022
DOI: 10.1111/1756-185x.14426
|View full text |Cite
|
Sign up to set email alerts
|

Ankle and foot pathologies in early rheumatoid arthritis, what can ultrasound tell us?

Abstract: Background Rheumatoid arthritis (RA) is a systemic autoimmune polyarticular disease. Despite being commonly affected in RA, the ankle and foot do not receive much attention, particularly in early disease. The precise diagnosis of their involvement and its impact on health is a clinical challenge that requires accurate assessment. Aim To determine the role of ultrasound in evaluation of ankle and foot pathologies and assess its impact on functional activity in newly diagnosed RA patients. Methods The study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(57 reference statements)
2
2
0
Order By: Relevance
“…Confirming our results, a study reported that BMI in patients with low DAS 28 was substantially lower than moderate DAS 28 participants [17] . Interestingly, a research indicated that US-observed ankle inflammation was substantially associated with RA activity.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Confirming our results, a study reported that BMI in patients with low DAS 28 was substantially lower than moderate DAS 28 participants [17] . Interestingly, a research indicated that US-observed ankle inflammation was substantially associated with RA activity.…”
Section: Discussionsupporting
confidence: 91%
“…In the present work, of the study participants, 38 (38%) participants had no symptoms, and 62 (62%) had symptoms, of them 9 (9%) participants were in right ankle, 15 (15%) participants were in left ankle, and 38 (38%) bilateral. Supporting our results, a study reported symptoms with 200 ankles 104 were without symptoms [17] . Parallel to our results, a study reported total of 97 painful ankles, while 63 ankles had no symptoms [19] .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations